Sosialisasi Digital Marketing Pada UMKM di Kota Blitar Sebagai Sarana Pengembangan Pemasaran Produk - Saniyyah Saniyyah; Tiara Febry Adviola; Ika Korika Swasti (JURNAL RISET MANAJEMEN (JURMA), 2023)
Technological changes affect decision-making, behavior, and the way humans communicate and act. The rapid development of digital technology has affected people's lives, especially in the world of marketing. The use of digital media in today's marketing activities has a major influence on the progress of a business. The need for insight and knowledge of business actors regarding today's digital technology. Business actors in Sukorejo Village and Klampok Village need to be briefed on implementing digital marketing in their business. Socialization activities were carried out in two sub-districts to provide insight and knowledge about the importance of digital marketing for the sustainability of their businesses. The implementation of this socialization was carried out using the lecture method and followed by a question and answer session and practice. With assistance in making Instagram, a module on how to create and use Instagram is provided. Providing digital marketing socialization for Blitar MSME actors to develop product marketing, Blitar MSME needs the development of social media as a means of promotion. The purpose of conducting this research is to provide an understanding of the importance of digital marketing for MSME actors in developing their business. The results of the MSME development assistance activities by organizing digital marketing socialization activities are the response and enthusiasm of the audience which is quite good in carrying out this activity.